Physical activity levels of patients with acute coronary syndrome - (:unkn) unknown (PROFESSIONAL MEDICAL PUBLICATIONS, 2011)
Objectives: Physical activity scales providing international comparisons were developed to assess physical inactivity. The purpose of this study was to investigate the physical activity levels of the patients with acute coronary syndrome (ACS) using International Physical Activity Questionnaire (IPAQ). Methodology: A total of 110 patients, 26 women and 84 men, who were willing to participate in the study were evaluated. These patients did not have communication problems, had a clear conscious, were aged twenty and above and were currently hospitalized in intensive care unit and diagnosed with ACS. Results: The mean age of the patients was 59.23+13.20. It was reported that the 65.5% of the patients did not exercise. Physical activity level of men was significantly higher than that of women in the work domain (p=.023), and active transportation domain (p=.006). There was a significant difference between body mass index (BMI) with total IPAQ score (p=.02). There was a significant difference between exercise performance of subjects and the active transportation domain (p=.01) score and between the leisure and the physical activity score (p=.0001). Conclusion: In Turkey, very few patients with ACS had sufficient level of physical activity which can protect health. Therefore, physical inactivity should be remembered as one of the adjustable major risk factors of ACS and active life style should be promoted.
Keywords: Acute Coronary Syndrome; nursing; physical activity; IPAQ; DISEASE; RISK